GAMBARAN KEPEMILIKAN RUMAH SEHAT DI WILAYAH KERJA PUSKESMAS SUNGAI DURIAN KABUPATEN KUBU RAYA - Natalina, Natalina; Rochmawati, Rochmawati; Elly, Trisnawati (JUMANTIK (Jurnal Mahasiswa dan Peneliti Kesehatan), 2015)
The percentages of the village-based healthy home at work area of Puskesmas Sungai Durian in 2012 encompassed a scope of 23032 houses. There have been 2303 houses (10%) inspected along this period. The total number of healthy homes are 1705 houses (74,03%) with 396 houses (78,57%) in Arang Limbung as the highest number of healthy homes. The lowest number of healthy homes are found in Desa Madu Sari with 62 houses (63,96%). The aim of this study was to find out an overview of the healthy home ownership at work work area of Puskesmas Sungai Durian Kabupaten Kubu Raya. This study was conducted by using descriptive method with univariate analysis as the technique of data collecting. The findings of the research taken from 100 respondents showed some compelling ideas. There were found 47,0% of ineligible ventilation condition and 53,0% of eligible ventilation condition. Subsequently, of 46.0% were found to be ineligible lighting at home and 54,0% for eligible lighting. The ineligible condition of humidity was 48,0%, and its eligible humidity was 52.0%. The problem of residential density issue emerged as there were found 33,0% ineligible residential density and 67,0% which fullfilled the eligibility of good residential density. The followings come closer to present that there were 84.0% of ineligible clean water and 16.0% of eligible clean water. The disposal of excreta was found to be 69.0% for its ineligibility and 31.0% for its eligibility. The disposal of wastewater also showed the highest percentege of its ineligibility with 74.0%; the eligibility was only 26.0%. The next issue of waste disposal showed the lowest percentage of the ineligibility among the preceded findings with 11.0% and 89,0% of its eligibility. Based on the findings, the local public health centers are encouraged to raise the awareness of the society concerning on the environmental issue particularly on the concept of healthy homes. One of which is how to improve knowledge and understanding in order to create a healthy home for their living.Keywords: ventilation, lighting, humidity, residential density, healthy home